Successful Treatment of Pediatric Generalized Pustular Psoriasis with Secukinumab - Yu K; Bao H; Wu X (Clinical, Cosmetic and Investigational Dermatology)
Keyi Yu,1 Huaye Bao,2 Xingang Wu2 1Department of Dermatology, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Dermatology, Hangzhou Third People’s Hospital, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xingang Wu, Department of Dermatology, Hangzhou Third People’s Hospital, 38 Xihu Road, Hangzhou, Zhejiang, 310009, People’s Republic of China, Tel +8657187827534, Fax +8657187827535, Email wuxingang1986@126.comAbstract: Generalized Pustular Psoriasis (GPP) is a rare, severe, life-threatening form of psoriasis and often resistant to conventional systemic therapy. It can be induced by deficiency of interleukin (IL)-36 receptor antagonist. Treatment of patients with GPP is often difficult, and there is no consensus on the best options available to date. However, multiple biologics approved for use in plaque-type psoriasis have also been used in GPP. Here, we report a 6-year-old boy with GPP who was misdiagnosed with AGEP and was treated with corticosteroids but did not respond well. He showed significant improvement following secukinumab treatment. Our case report indicates that IL-17A inhibition as a promising therapeutic option for pediatric GPP without combination with other systemic agents.Keywords: juvenile pustular psoriasis, biologics, interleukin 17, secukinumab